Does the response to aspirin and clopidogrel vary over 6 months in patients with ischemic heart disease?. (23rd April 2015) - Khanna, V.; Mikael, R.; Thayalasamy, K.; Sambu, N.; Dimitrov, B. D.; Englyst, N.; Calver, A. L.; Corbett, S.; Gray, H.; Simpson, I. A.; Wilkinson, J. R.; Curzen, N.
Summary Background Dual‐antiplatelet therapy (DAPT) with aspirin and a P2Y12 inhibitor, mostly clopidogrel, is the default therapy in both acute coronary syndrome (ACS) and after intracoronary stents. It is well established that responses to antiplatelet therapy (APT), particularly clopidogrel, are subject to considerable interindividual variability. Objectives We investigated whether responses to APT in individuals vary significantly over time. Methods Simultaneous assay with VerifyNow™ and short thrombelastography (s‐TEG) was performed before and at four time points over 6 months after hospital discharge in 40 patients receiving DAPT. Serum thromboxane B2 levels were also measured. Results While aspirin response units (ARU) by VerifyNow™ and serum thromboxane B2 levels remained stable over time, arachidonic acid (AA)–mediated platelet aggregation with s‐TEG (i.e. area under the curve at 15 min in AA channel, AUC15AA) increased at 1 week compared with predischarge (P < 0.008). In addition, platelet reactivity units (PRU) by VerifyNow™ (P = 0.046) and adenosine diphosphate (ADP)–mediated platelet aggregation with s‐TEG (i.e. AUC15ADP) also increased at 1 week compared with predischarge (P = 0.026). There were no significant changes in either platelet reactivity or rates of high on‐treatment platelet reactivity while receiving clopidogrel beyond 1 week. Conclusions This study demonstrates important variability in responses to APT within individuals between predischarge and 1 week but not thereafter. The use of a single early (predischarge) platelet function assay as an indicator of future response may therefore be flawed. The design of future strategies to assess individual responses for tailored therapy needs to take this into account.